Laryngeal Cryptococcosis Associated With Inhaled Corticosteroid Use: Case Reports and Literature Review - Wong, Daniel Jun Yi; Stanley, Peter; Paddle, Paul (Frontiers in Surgery, 2017)
Laryngeal cryptococcosis is a rare clinical entity. There have been a limited number of case reports in the literature with no consensus regarding optimal management. This review contributes two additional case reports of immunocompetent patients with cryptococcal infection of the larynx in whom exposure to high doses of inhaled corticosteroids is proposed as a significant risk factor. Twenty cases were identified from review of the literature. All patients presented with hoarseness, and a spectrum of microlaryngoscopic features, often mimicking laryngeal malignancy. The majority of cases were treated with systemic antifungal therapy, three cases had surgical excision alone, and another 3 had a combination of medical and surgical management. Risk factor modification, in the form of a reduction in inhaled corticosteroid was employed in the two new cases, and in some previously published cases. Risk factor modification, such as reduction of inhaled corticosteroid dose, in addition to oral antifungal agents can be effective in managing cryptococcal laryngitis.